2019
DOI: 10.1016/j.jtcme.2017.07.001
|View full text |Cite
|
Sign up to set email alerts
|

Anti-ulcer effect of Gallarhois extract with anti-oxidant activity in an ICR model of ethanol/hydrochloride acid-induced gastric injury

Abstract: Gallarhois (GR) is a traditional oriental herbal medicine with various pharmacological effects; however, its effect on gastric ulcer has not been previously explored. We firstly investigated the component and antioxidant activity of GR extract (EtGR) by HPLC analysis and 1,1-diphenyl-2-picrylhydrazyl (DPPH) assay. The results showed that EtGR consisted of gallotannin (68.7%), gallic acid (27.2%) and methyl gallate (4.1%) and that it had a high antioxidant value (IC50 value; 1.93 μg/mL). To evaluate the possibl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
11
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(12 citation statements)
references
References 38 publications
1
11
0
Order By: Relevance
“…In gastric ulcer, HCl/ethanol causes inflammation to initiates macrophages release and inflammatory cytokines (TNF-α, IL-1β, and IL-6) to promote neutrophil accumulation at the target site for instigation of mucosal barrier destruction [24]. This data was in a line with a study conducted on gallic acid against ethanolinduced gastric ulcer rats which shows its anti-inflammatory effect by inhibiting the levels of TNF-α and IL-6 elevation [25]. Pro-inflammatory cytokine TNF-α activates the NF-kβ pathway, triggering the transcription for macrophages and cytokines to mediate inflammation.…”
Section: Discussionsupporting
confidence: 75%
“…In gastric ulcer, HCl/ethanol causes inflammation to initiates macrophages release and inflammatory cytokines (TNF-α, IL-1β, and IL-6) to promote neutrophil accumulation at the target site for instigation of mucosal barrier destruction [24]. This data was in a line with a study conducted on gallic acid against ethanolinduced gastric ulcer rats which shows its anti-inflammatory effect by inhibiting the levels of TNF-α and IL-6 elevation [25]. Pro-inflammatory cytokine TNF-α activates the NF-kβ pathway, triggering the transcription for macrophages and cytokines to mediate inflammation.…”
Section: Discussionsupporting
confidence: 75%
“…ROS stimulated in the presence of ethanol are responsible for lipid peroxidation and chemotaxis of inflammatory cells to the injury site. Ethanol induces leukocyte recruitment that stimulates inflammatory responses by increasing levels of pro-inflammatory cytokines such as TNF-α and IL-1β ( Song et al, 2019 ).…”
Section: Discussionmentioning
confidence: 99%
“…MDA is one of the most common markers of lipid peroxidation and oxidative stress that can be quantified in ulcerated and inflammatory lesions of the gastrointestinal tract ( Song et al, 2019 ). The results obtained showed that the lipid peroxidation induced by ethanol was reduced by pre-treatment with (-)-Carveol.…”
Section: Discussionmentioning
confidence: 99%
“…Antioxidants including SOD, CAT, and GSH can scavenge oxygen-derived free radicals in the gastric mucosa [37]. Depletion of cellular GSH levels, as well as reduced SOD and CAT activities, impedes recovery shortly after EtOH-induced gastric oxidative injury [38][39][40]. Increases in SOD, GSH, and CAT levels of the gastric tissues contribute to gastroprotection against indomethacin and to the healing of acetic acid-induced gastric mucosal injury [41][42][43].…”
Section: Discussionmentioning
confidence: 99%